Persona-ization: Searching on Behalf of Others - Bennett, Paul; Fishkov, Alexander; Kiciman, Emre (Proceedings of the SIGIR 2015 International Workshop on Social Personalisation & Search (SPS'15), 2015)
Many information retrieval tasks involve searching on behalf of others. Example scenarios include searching for a present to give a friend, trying to find “cool” clothes for a teenage child, looking for medical supplies for an elderly relative [1], or planning a group activity that many friends will enjoy. In this paper, we use demographically annotated web search logs to present a large-scale study of such “on behalf of” searches. We develop an exploratory technique for recognizing such searches, and present information to describe and understand the phenomenon, including the demographics of who is searching, who they are searching for and on what topics.